2001
DOI: 10.1038/sj.onc.1204445
|View full text |Cite
|
Sign up to set email alerts
|

Detection of repair activity during the DNA damage-induced G2 delay in human cancer cells

Abstract: All eukaryotic cells manifest cell cycle delay after exposure to DNA damaging agents. It has been proposed that such cell cycle checkpoints may allow DNA repair but direct evidence of such activity during the radiation-induced G2 delay has been lacking. We report here that cells arrested in G2 by radiation (2 ± 3 Gy) and etoposide incorporate bromodeoxyuridine (BrdU) at discrete foci in the nucleus. We detected G2 cells with CENP-F, a nuclear protein maximally expressed in G2. Ca eine and okadaic acid, both es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 46 publications
5
58
0
Order By: Relevance
“…More recently, we also observed that TSA abrogated radiation-induced G 2 -M arrest and increased apoptosis (45). Abrogation of the radiation-induced G 2 -M arrest by class-specific HDI was seen again in this report, which we speculate may decrease the time available for repair of DNA damage or may interfere with repair mechanisms (47). Abrogation of the radiation-induced G 2 delay mediated by caffeine or staurosporin has also been noted to shift the pathway of cell death from mitotic death to apoptotic death (48).…”
Section: Discussionsupporting
confidence: 55%
“…More recently, we also observed that TSA abrogated radiation-induced G 2 -M arrest and increased apoptosis (45). Abrogation of the radiation-induced G 2 -M arrest by class-specific HDI was seen again in this report, which we speculate may decrease the time available for repair of DNA damage or may interfere with repair mechanisms (47). Abrogation of the radiation-induced G 2 delay mediated by caffeine or staurosporin has also been noted to shift the pathway of cell death from mitotic death to apoptotic death (48).…”
Section: Discussionsupporting
confidence: 55%
“…Our own experiments illustrated that, even for similar levels of p53 induction/stabilization, the p21 WAF1/Cip1 response in PrEC is greatly attenuated in comparison to its stromal counterpart. While the p53/ p21 WAF1/Cip1 responses for our panel of malignant cell lines were as previously reported, the LNCaP cell line's 52 and cellular survival following radiation. 53 Indeed, although our results suggest increased survival for cells which lack the G1 checkpoint, defined studies in isogenic tissue culture or solid tumor models which differ in p53 status and specific G1, S and G2 checkpoint control experiments are required to prove this hypothesis, and are part of a current research program.…”
Section: Discussionmentioning
confidence: 70%
“…For ZR-75-1 and H-466B cells, this global increase is, respectively, 41.4 and 41.5. Kao et al (2001) showed that DNA damage-induced G 2 delay was strongly associated with DNA repair activity in human cancer cells. We can hypothesize that, after irradiation, progesterone leads to the inhibition of the G 2 checkpoint that normally arrests the cell cycle and permits cells to repair DNA damage and/or to undergo apoptosis if the level of unrepaired DNA is too high.…”
Section: Discussionmentioning
confidence: 99%